Wind characteristics at a long-span sea-crossing bridge site based on monitoring data. Issue 3 (September 2020) - Zhou, Yi; Sun, Limin; Xie, Mowen
Six years of wind data are used to investigate the statistical characteristics of general and strong winds acting on the Donghai Bridge, a sea-crossing bridge in China. The general wind at the bridge site shows a relatively stable annual repeatability, and the discrepancies are found between the measured wind field parameters and those suggested by the design code. For strong winds, both the 10-min mean wind speed and the turbulent variance greatly exceed those of general winds, while the turbulence intensity, integral length scale, and gust factor do not exhibit any noticeable quantitative trends. The measured wind spectra of both general and strong winds show a shift toward the high-frequency range compared with Simiu's spectrum (along-wind direction). The wind measurements at the bridge site are easily interfered with the bridge structure itself, resulting in a greater turbulence along the bridge axis and a higher turbulent kinetic energy in the high-frequency range, which needs to be considered in designing structural health monitoring systems in the future. This study provides field evidence for the wind-resistant design and evaluation of long-span sea-crossing bridges.